Toxicity of Tangiayu Incense Smoke as an Insecticide Against Aedes aegypti Mosquito Mortality - I Made Dwi Mertha Adnyana; I Putu Sudiartawan; Ni Luh Gede Sudaryati (MEDIA ILMU KESEHATAN, 2021)
Background: Natural substances such as beluntas leaves, lemongrass leaves, and wood powder packaged in Tangiayu incense can be used to control vectors.Objective: This study was to determine the toxicity of Tangiayu smoke insecticides on Aedes aegypti mosquito mortality.Methods: Experimentation with a completely randomized design was applied to eight hundred seventy-five mature Aedes aegypti mosquitoes, divided into seven treatment groups with five replications, each unit consisting of 25 mosquito tests (n = 25). The data was collected from Aedes aegypti mosquito mortality following exposure to Tangiayu incense smoke for 5, 10, 15, 20, and 25 minutes. The ANOVA, LSD, and Probit tests were used to examine mortality data. Results: According to the research, there was an increase in Aedes aegypti mosquito mortality following the exposure smoke Tangayu incense. The exposure duration that resulted in 50% mortality was 18 min 30 s (LT50=5.9011), which is classified as extremely hazardous. The probit test resulted in equation 5= 0.0582x + 5.627. The coefficient of determination (R2) is 0.9718 (97.18%) and the coefficient correlation (r) is 0.9858 (98.58%).Conclusion: Exposure to Tangiayu incense smoke on Aedes aegypti mosquitoes mortality is extremely hazardous and effectively used as insecticides.